A study of clinical profile and outcome of pneumonia associated with traditional child rearing practices in infants - Kulkarni, Nagamani; Ukkali, Sadashiva B.; Gangawati, Sujay P.; Shetty, Prasanna K.; Thobbi, A. N. (International Journal of Contemporary Pediatrics, 2023)
Background: Customs and traditions are strictly followed in many Indian families, both rural and urban. Certain established child rearing practices are being advocated by elders and are being followed traditionally even today. Many of these practices play a significant role in causing pneumonia in children. This study was undertaken to compare and assess the clinical features and outcome of pneumonia occurring in children with traditional rearing practices and in infants without traditional child rearing practices and various factors influencing them. Methods: The present study is a prospective case control study, done in the department of paediatrics, Al-Ameen Medical College and Hospital Vijayapura, in which a total of 220 infants with clinical and/or radiological signs of pneumonia were enrolled during the period of March 2022 to February 2023. Results: 73 out of 220 infants (33%) with pneumonia had history of traditional child rearing practices. Demographic factors like combined families, young and illiterate mothers, lower socioeconomic status, domiciliary deliveries were found to be statistically significant. Increased clinical severity and prolonged outcome (60.4%) and complications (42.5%) were found to be more in pneumonia in infants associated with traditional child rearing practices. Conclusions: This study showed increased clinical severity and prolonged outcome and more complications of pneumonia in infants associated with traditional child rearing practices. High mortality (7.5%) was also seen. Most common traditional child rearing practices influencing outcome in infants are oil bath and blowing into the nose. Thus there is an urgent need to systematically study the utility, futility and possible dangers of a large number of traditional child rearing practices followed in infants.